Da’wah Thoughts of Hasan Al Banna and Said Nursi: A Comparative Research in Islamic Education Perspective - Yusof, Ahmad Syafiq; Jimaâain, Muhammad Talhah Ajmain; Shukor, Muhammad Hazwan Mohd (International Journal of Islamic Khazanah, 2022)
Islamic education has been strongly emphasized in Muslim communities. The quality of education and adherence to the Islamic world view will shape Muslim personalities toward the true meaning of excellence in this world and the hereafter. This article discusses and introduces the efforts of Tawhid purification from an Islamic Education perspective undertaken by Hassan Al Banna (1906-1949 AD) and Badiuzzaman Said Nursi (1877–1960 AD) to address emergent problems within the Egyptian and Turkish Muslim community in early 20th century whereby the absorption of values and thought outside the authenticity of Islam had successfully influenced society thinking in terms of religious beliefs and practices. Therefore, both Hassan Al Banna and Said Nursi offered a solution to this problem by implementing measures to purify tawhid in society. This article analyses their efforts in tawhid purification in implementing da’wah dictates in Egypt and Turkey. To achieve this goal, the historical analysis method is utilized to discuss the efforts of Hassan Al Banna and Said Nursi and present a critical examination of their efforts to save the tawhid of Muslims and ensure they return to the true teachings of Islam. The results of this study highlight Hassan Al Banna and Badiuzzaman Said Nursi as da’wah figureswho contributed to tawhid purification in the Islamicworld. At the same time, the findings could be used as guidelines for the religious, preachers, and researchers to propose tawhid purification as an important da’wah effort in society today.